The monk on the roof: the story of an Ethiopian manuscript found in Jerusalem (1904) - Ancel, Stéphane (Open Jerusalem, 2022)
Introduction : A Historical Emergency : The Paradoxical Posterity of a Failed Manuscript - Dayr al-Sultan : A Rooftop Monastery - An Enigmatic Unpublished Manuscript - The Archaeology of a Militant Propaganda Text - Conflicts and Protections: 1850-1903 - With Memory as His Only Weapon - The Reflection of an Ethiopia in Transformation - The Ethiopians in a Global City - Conclusion : The Keys to Power : The Ethiopians at the Doors of the Sanctuary